Powell-Smith & Furmston's building contract casebook - Furmston, M. P. (Oxford ; Malden, MA : Blackwell Pub., 2006)
This well established reference book brings together leading cases on building contracts to illustrate legal principles. It provides a statement of the principle established, a summary of the facts and the decision and, for most cases, a verbatim extract of the judgment. The latest edition includes a number of new cases since the last edition was published in 1999.
Minimalist Syntax; Contents; Acknowledgments; List of Contributors; Introduction; 1 On Control; 2 On Logical Form; 3 Steps toward a Minimal Theory of Anaphora; 4 Syntactic Variation, Historical Development, and Minimalism; 5 Phrase Structure; Index.
Includes index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Construction contracts -- England -- Cases; Construction contracts -- Wales -- Cases; Grammar, Comparative and general -- Syntax; Minimalist theory (Linguistics); Syntaxe; Minimalisme (Linguistique); LAW -- Military; Minimalist theory (Linguistics); Grammar, Comparative and general -- Syntax; Construction contracts; England; Wales; Kontrolle; Bewegung; Bewegungstransformation; Logische Form; Bindungstheorie; X-Bar-Syntax; Anapher; Wortstellung; Sprachwandel; Phrasenstruktur; Minimalist program; Syntax; Theorie; Minimalist program; Syntaxis; Trials, litigation, etc